2021
DOI: 10.30998/npjpe.v3i1.684
|View full text |Cite
|
Sign up to set email alerts
|

Analisis pembelajaran daring pada materi dinamika partikel ditinjau dari komunikasi matematis

Abstract: This study aims to analyze the achievement of each indicator that measures students' mathematical understanding abilities in basic physics courses on particle dynamics material. This research is a qualitative descriptive study that seeks to describe the analysis of students' mathematical understanding abilities. The research subjects were 6 class 3 semester students of biology education consisting of 198 students. The data collection method used includes tests of students' mathematical understanding abilities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The mathematical communication ability of junior high school students in Cimahi city is low according to research (Wijayanto, et al, 2018) on triangle and quadrilateral material, which is followed by research (Niasih, et al, 2019) for statistical material. Further research (Aminah, et al, 2018) demonstrates that in the identified literature, the mathematical communicat According to Supriyatin et al (2021), current data indicate that students' mathematical communication ability are still lacking.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The mathematical communication ability of junior high school students in Cimahi city is low according to research (Wijayanto, et al, 2018) on triangle and quadrilateral material, which is followed by research (Niasih, et al, 2019) for statistical material. Further research (Aminah, et al, 2018) demonstrates that in the identified literature, the mathematical communicat According to Supriyatin et al (2021), current data indicate that students' mathematical communication ability are still lacking.…”
Section: Introductionmentioning
confidence: 98%
“…2020 (Junedi & Sari). According to Supriyatin (2021), to increase students' capacity for understanding mathematical communication, it is necessary to ask them several questions that are relevant to daily life and are therefore simple to comprehend. The researcher wants to know the impact of interactive multimedia-based learning on students' mathematical communication ability in the algebraic structure course.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation